Effects of Angiotensin Converting Enzyme Inhibition or Angiotensin Receptor Blockade in Dialysis Patients. Issue 3 (January 2015) - Wu, Cho-Kai; Yang, Yao-Hsu; Juang, Jyh-Ming Jimmy; Wang, Yi-Chih; Tsai, Chia-Ti; Lai, Ling-Ping; Hwang, Juey-Jen; Chiang, Fu-Tien; Chen, Pau-Chung; Lin, Jiunn-Lee; Lin, Lian-Yu; Wang., Hsueh hwa
<x xml:space="preserve">Abstract</x> Abstract Long-term benefit of using a renin–angiotensin–aldosterone system blocker such as an angiotensin-converting enzyme inhibitor (ACEI) or an angiotensin II receptor blocker (ARB) for patients already receiving dialysis remains undetermined. The aim of this study is to assess the efficacy and safety of ACEI or ARB use in dialysis patients. We performed a population-based cohort study with time-to-event analyses to estimate the relation between the use of ACEI/ARB and their outcomes. We used a nationwide database (Registry for Catastrophic Illnesses) for Taiwan, which has data from 1995 to 2008 nearly of all patients who received dialysis therapy. The records of all dialysis patients aged ≥18 with no evidence of cardiovascular (CV) events in 1997 and 1998 (133, 564 patients) were examined. Users (n = 50, 961) and nonusers (n = 59, 913) of an ACEI/ARB were derived. We then used propensity score matching and Cox proportional hazards regression models to estimate adjusted hazard ratios (HRs) for all-cause mortality and CV events in users and nonusers of an ACRI/ARB. The 15, 182 patients, who used an ACEI/ARB, and the 15, 182 nonusers had comparable baseline characteristics during the 14 years of follow-up. The mortality was significantly greater in patients who did not use an ACEI/ARB (HR = 0.90, 95% confidence interval = 0.86–0.93). Subgroup analysis of 3 tertiles of patients who used different total amounts of ACEI/ARB during the study period indicated that CV events were more common in patients who used an ACEI/ARB for a short duration (tertile 1: HR = 1.63), but less common in those who used an ACEI/ARB for long durations (tertile 2: HR = 1.05; tertile 3: HR = 0.94; trend for declining HR from tertile 1 to 3: P < 0.001). The mortality benefit provided by use of an ACEI/ARB was consistent across most patient subgroups, as was the benefit of ARB monotherapy rather than ACEI monotherapy. Independent of traditional risk factors, overall mortality was significantly lower in dialysis patients who used an ACEI/ARB. In addition, subjects who used an ACEI/ARB for longer durations were significantly less likely to experience CV events.